2021
DOI: 10.1186/s12984-021-00976-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient, carer, and staff perceptions of robotics in motor rehabilitation: a systematic review and qualitative meta-synthesis

Abstract: Background In recent years, robotic rehabilitation devices have often been used for motor training. However, to date, no systematic reviews of qualitative studies exploring the end-user experiences of robotic devices in motor rehabilitation have been published. The aim of this study was to review end-users’ (patients, carers and healthcare professionals) experiences with robotic devices in motor rehabilitation, by conducting a systematic review and thematic meta-synthesis of qualitative studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Literature on innovative rehabilitation technology such as virtual reality has shown that it was useful in reducing neuropathic pain ( 29 ), enhancing rehabilitation of upper limb function ( 30 ), balance, motor recovery, as well as helping to improve user morale and participation among individuals with SCI ( 31 ). In a recent systematic review, most rehabilitation service users and caregivers found that the use of robotics in motor rehabilitation were beneficial to the physical, psychological and social well-beings, and it was well-accepted ( 32 ). The availability of smart home technology also tended to increase the independence and quality of life among persons with impairment ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature on innovative rehabilitation technology such as virtual reality has shown that it was useful in reducing neuropathic pain ( 29 ), enhancing rehabilitation of upper limb function ( 30 ), balance, motor recovery, as well as helping to improve user morale and participation among individuals with SCI ( 31 ). In a recent systematic review, most rehabilitation service users and caregivers found that the use of robotics in motor rehabilitation were beneficial to the physical, psychological and social well-beings, and it was well-accepted ( 32 ). The availability of smart home technology also tended to increase the independence and quality of life among persons with impairment ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, a comprehensive summary of patients' likes, dislikes and preferences for specific upper limb rehabilitation robots is fundamental when outcomes among the types of robots are largely similar. 8 The only systematic review to date that aimed to metasynthesise end-user perceptions of robotics is in motor rehabilitation 20 and provides an early, generic description of the patients', caregivers' and professionals' experiences with rehabilitation robots. In the review by Laparidou et al, an overview of all types of motor rehabilitation using rehabilitation robots for various clinical conditions (shoulder instability/rotator cuff injury, spinal cord injury, stroke, brain injury, cerebral palsy and unspecified clinical conditions) of all ages (from five to 84 years of age) is provided.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In the review by Laparidou et al , an overview of all types of motor rehabilitation using rehabilitation robots for various clinical conditions (shoulder instability/rotator cuff injury, spinal cord injury, stroke, brain injury, cerebral palsy and unspecified clinical conditions) of all ages (from five to 84 years of age) is provided. 20 This review’s inclusion of participants with varied clinical presentations offers valuable insight into their generalised experiences with rehabilitation robots. However, as the review focuses on a broad clinical group, it fails to provide a comprehensive focus and in-depth description of rehabilitation robots’ use in adult patients with stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders’ perceptions of robotics in motor rehabilitation are reported by qualitative meta-synthesis, to be generally acceptable, useful and beneficial (physically, psychologically, and socially) in rehabilitation 20 . However, this review included only one qualitative study specifically focussed on gait rehabilitation after stroke 21 , including only individuals in the chronic phase of stroke.…”
Section: Introductionmentioning
confidence: 99%